(untitled) (Journal of International Studies, 2020)
Uganda lies in the heart of Sub-Saharan Africa. It is situated in East Africa and occupies an area of 241,038 sq km (roughly twice the size of the state of Pennsylvania) and its population is about 35,873,253 (CIA World Factbook, 2012). Uganda is bordered by Tanzania and Rwanda to the south, Democratic Republic of Congo to the west, South Sudan to the north, and Kenya to the east. Uganda is a landlocked country and occupies most of the Lake Victoria Basin, which was formed by the geological shifts that created the Rift Valley during the Pleistocene era. Uganda was a British colony and became an independent- sovereign nation in 1962 without a bloody struggle. Several ethnic groups reside in the country i.e. Baganda, Banyankole, Bahima, Bakiga, Bunyoro, Batoro, Basoga, Bagisu, Langi, Acholi, Lugbara, Karamojong and others. English is the official language by virtue of Article 6(1) of the 1995 Constitution and Swahili is also widely spoken especially in the urban areas. Uganda has no State religion. As a country, Uganda has witnessed some positive development in the area of security. The government managed to plant the seeds of peace in the north by defeating the Lord Resistance Army (LRA) led by Joseph Kony.